The Impact of Innovation Process on the Life Cycle of the Economic Development of a Resource-Based Region - AVRAMCHIKOVA, Nadezhda Timofeevna; AVRAMCHIKOV, Vaycheslav Mihajlovich; BELYAKOVA, Galina Yakovlevna; BELYAKOV, Sergey Andreevich (Journal of Advanced Research in Law and Economics, 2016)
The economic activity of any socio-economic system is cyclical. The life cycle of the economic development of a region goes through the stages of recovery, expansion, maturity, recession and depression and is formed under the influence of intelligence, reflection and the mission of a territory. The formation of the life cycle of the economic development of a region is largely determined by the stages of recovery and expansion of its economy. The embryonic stage of the development of a technological mode, emerging in the context of the prevalence of the previous technological mode, corresponds to the stage of the recovery of the economy of a region. The stage of maturity corresponds to the stage of the expansion of the economic development of a region during which the new technological mode replaces the previous one and becomes the main factor of economic growth and the stabilization of the economy of a region. The stage of decline of the current technological mode inevitably causes the recession in the economic development of a region and the subsequent depression. The innovation processes which take place in the economy of a region during the stages of recovery and expansion have a positive impact on the life cycle of the economic development of a region and are a fundamental factor in ensuring stability and competitiveness of regional economy. The life cycle of the economic development of a resource-based region has its specifics, since the economy of this type of regions is characterized by a focal type of development, so the innovative processes in this economy have a pronounced local character.
Keywords: life cycle of economic development; resource-based region; technological mode; innovation processes